2013
DOI: 10.1016/j.neuroimage.2012.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Language experience differentiates prefrontal and subcortical activation of the cognitive control network in novel word learning

Abstract: The purpose of this study was to examine the cognitive control mechanisms in adult English speaking monolinguals compared to early sequential Spanish-English bilinguals during the initial stages of novel word learning. Functional magnetic resonance imaging during a lexico-semantic task after only two hours of exposure to novel German vocabulary flashcards showed that monolinguals activated a broader set of cortical control regions associated with higher-level cognitive processes, including the supplementary mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 47 publications
(97 reference statements)
4
37
0
Order By: Relevance
“…This process, comprising implicit and explicit learning associated with sensorimotor representations, is still poorly understood. Among others, it engages basal ganglia circuits targeting mesiofrontal cortex as has been shown in studies on the learning of novel words (Bradley et al, 2013) or novel phonetic contrasts (Callan et al, 2003). During speech generation, conversely, the ability to transform abstract linguistic representations into executable motor programs can be considered as a process transforming declarative information structures into procedural representations, which is performed in a highly automatized way and also includes subcortical circuits.…”
Section: Sma and Pre-sma As An Interface Between Procedural And Declamentioning
confidence: 94%
“…This process, comprising implicit and explicit learning associated with sensorimotor representations, is still poorly understood. Among others, it engages basal ganglia circuits targeting mesiofrontal cortex as has been shown in studies on the learning of novel words (Bradley et al, 2013) or novel phonetic contrasts (Callan et al, 2003). During speech generation, conversely, the ability to transform abstract linguistic representations into executable motor programs can be considered as a process transforming declarative information structures into procedural representations, which is performed in a highly automatized way and also includes subcortical circuits.…”
Section: Sma and Pre-sma As An Interface Between Procedural And Declamentioning
confidence: 94%
“…However, some studies have also found a role for the putamen in cognitive control (Ell, Hélie, & Hutchinson, 2012). This distinction between direct motor responses and planning was evident in the brain activity seen when directly comparing monolinguals and bilinguals by Bradley et al (2013). Increased activity in the putamen in bilinguals suggests that they either engage in cognitive or motor control when making semantic decisions to the newly learned words.…”
Section: Introductionmentioning
confidence: 96%
“…A group of adult Spanish-English bilinguals and English monolinguals were taught a set of German written words that were not orthographically related to Spanish (Bradley, King, & Hernandez, 2013). After learning the words to 90% accuracy, participants were placed in an MRI scanner and asked to make a living/nonliving judgment on the German words that were intermixed with a set of English words.…”
Section: Introductionmentioning
confidence: 99%
“…However, such plastic changes are often not restricted to single brain compartments, but rather affect a vast amount of cortical tissue (James et al, 2013;Zou et al, 2012;Bermudez et al, 2009;Abutalebi & Green, 2007;Gaser & Schlaug, 2003a, 2003b. This phenomenon probably accounts for the often observed cognitive advantages of music and language experts in a variety of cognitive domains, including verbal learning (Bradley, King, & Hernandez, 2013;Kuhnis, Elmer, Meyer, & Jancke, 2013), memory (Morales, Calvo, & Bialystok, 2013;Kraus, Strait, & Parbery-Clark, 2012;Schulze, Zysset, Mueller, Friederici, & Koelsch, 2011), attention (Strait, Kraus, Parbery-Clark, & Ashley, 2010;Costa, Hernandez, & Sebastian-Galles, 2008;Bialystok, Craik, Klein, & Viswanathan, 2004), and inhibition (Festman, Rodriguez-Fornells, & Munte, 2010;Bialystok et al, 2004).…”
Section: Introductionmentioning
confidence: 99%